PENGARUH PENEMPATAN KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA KANTOR BPJS CABANG MANOKWARI - Brihancya, Monica; Bajari, Makarius; Usman, Sarah (Bisma: Jurnal Bisnis dan Manajemen, 2024)
This study aims to examine the impact of work placement and work experience on employee productivity, both partially and simultaneously. The research employs a quantitative analysis approach. A total of 38 samples were included in this study, and non-probability sampling was utilized for data collection. The primary data were gathered through a questionnaire, while secondary data were obtained from relevant journals and books. The method employed for data analysis is multiple linear regression, conducted using SPSS statistical software. The analysis results indicate that both work placement and work experience have a partial effect on employee productivity. Additionally, the ANOVA test results show that work placement and work experience simultaneously influence employee productivity at the BPJS Health Office in Manokwari. Based on the findings, it is recommended that the company prioritize selecting prospective employees who possess a solid understanding of relevant knowledge during the recruitment process.